THE EFFECTIVENESS OF THE TEACHER'S ROLE IN HELPING LEARNING DURING PANDEMIC IN KB IT INSAN HARAPAN - Oktavia Sari; Fuad Arif Noor (STPI Bina Insan Mulia Yogyakarta, 2022)
This study aims to determine the role of accompanying teachers and their effectiveness in helping learning during the pandemic at KB IT Insan Harapan. The subjects of this study were classroom teachers and their accompanying teachers. Informants from the Principal, teachers and employees at KB IT Insan Harapan, using qualitative methods with a qualitative descriptive approach. Data collection techniques using observation, interviews, and documentation. The results of this study from several respondents indicated that the role of the accompanying teacher was to help class teachers in planning lessons, preparing learning tools and media and being role models for students. The role of the assistant teacher during the pandemic at KB IT Insan Harapan is very effective for classroom teachers because they can carry out their duties and functions professionally. The effectiveness of this accompanying teacher is felt for classroom teachers, because their responsibilities become lighter with the assistance of the role of the accompanying teacher.